Izvori totalitarizma Hane Arent i njene refleksije na bošnjačko političko i humanitarno pitanje / Hannah Arendt's "The Origins of Totalitarianism" and her Reflections on the Bosnian Political and Humanitarian Issue - Halilović, Semir (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
This text refers to a review of the book The Origins of Totalitarianism by Hannah Arendt; Feminist Publishing House, Belgrade, 1998.